An application of marital horizon theory to dating violence perpetration - Johnson, Matthew David (Kansas State University, 2009)
An individual’s desire to marry and ideal age of marriage, two elements of the marital horizon theory, are examined in relation to dating violence perpetration, both physical assault and psychological aggression, in the present study using a sample of 611 college students from a large Midwestern university. Looking at the possible predictive power that the marital horizon variables might have on dating violence perpetration, above and beyond other known predictors of dating violence, could reveal an important area of investigation in both the emerging adulthood literature and the dating violence literature. Results indicate that victimization of dating violence accounted for the vast majority of the variance in perpetration of dating violence. Desire to marry emerged as a significant predictor of women’s perpetration of psychological aggression only when the victimization variables were excluded from the regression equation.
Keywords: marital horizon theory; dating violence perpetration; emerging adults; Health Sciences, General (0566)